2008
DOI: 10.1186/1546-0096-6-s1-p46
|View full text |Cite
|
Sign up to set email alerts
|

Time to treatment as an important factor for the response to methotrexate in juvenile idiopathic arthritis

Abstract: Methotrexate (MTX) is the most commonly used disease modifying antirheumatic drug (DMARD) in juvenile idiopathic arthritis (JIA), especially in polyarticular arthritis. At present no reliable prediction of individual response to MTX can be made. Identification of factors that influence the response to MTX could be helpful in realizing the optimal treatment for each individual patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 0 publications
1
34
1
1
Order By: Relevance
“…Whilst a diagnosis of JIA cannot be made before 6 weeks of symptoms, all children with suspected JIA should be referred to a paediatric rheumatologist for further assessment. Referral should be made without delay in suspected JIA; a retrospective cohort study of 128 children treated with methotrexate, a commonly used agent in JIA, showed that time from diagnosis to initiation of methotrexate was an important factor in response to treatment [81]. Whilst the blood tests listed earlier are useful in diagnosing JIA and subtyping the disease, normal blood test results do not preclude a diagnosis of JIA and should not prevent referral to a paediatric rheumatologist.…”
Section: Juvenile Idiopathic Arthritismentioning
confidence: 94%
“…Whilst a diagnosis of JIA cannot be made before 6 weeks of symptoms, all children with suspected JIA should be referred to a paediatric rheumatologist for further assessment. Referral should be made without delay in suspected JIA; a retrospective cohort study of 128 children treated with methotrexate, a commonly used agent in JIA, showed that time from diagnosis to initiation of methotrexate was an important factor in response to treatment [81]. Whilst the blood tests listed earlier are useful in diagnosing JIA and subtyping the disease, normal blood test results do not preclude a diagnosis of JIA and should not prevent referral to a paediatric rheumatologist.…”
Section: Juvenile Idiopathic Arthritismentioning
confidence: 94%
“…The observation that the achievement of better outcomes was related with earlier treatment introduction has been reported previously for methotrexate and sulfasalazine. 5,6 In this study, the strongest association with a poor response to etanercept was the systemic-onset JIA. Systemic-onset JIA patients had 3-times higher odds to achieve a poor treatment outcome compared with the nonsystemic JIA categories and more systemic-onset JIA patients discontinued etanercept over time.…”
Section: Commentmentioning
confidence: 96%
“…Methotrexate is an effective treatment for juvenile idiopathic arthritis (JIA) and is the most commonly used disease-modifying antirheumatic drug (DMARD) for this disease [9,10]. When treatment with methotrexate is not efficacious, other immunosuppressive agents or biological drugs are usually prescribed.…”
Section: Introductionmentioning
confidence: 99%